Millennial landscape and tourist development in China. The case of the Hani rice terraces in Yunnan - Myriam Dao (Via@)
Between 1995 and 2015, I conducted fieldwork in a rice-growing village in southwest China as an artist-researcher. In this text, I examine the profound changes taking place in rural border areas inhabited by non-Han minorities, and particularly those of the Hani in the Yunnan Red River Valley. What future is there for the Hani ancestral model of irrigated rice terraces, and what are the stakes? My work combines a sensitive approach through diverse artistic representations of landscapes – from classical Chinese art to the works of contemporary artists, including mine – and examines landscape planning and patrimonial policies. The conservation stakes are not only environmental – biodiversity, sustainable development – but also identity-based through vernacular and minority cultures. I will point out the limits of this landscape planning and outline its future.